Cortisol (stress) level of sutchi catfish (pangasianodon hypophthalmus) juvenile under different light wavelengths and intensities - Yusoff, Nor Amira; Mukai, Yukinori; Sallehudin, Muhammad Firdaus; Nai, Han Tan; Mohammad Noor, Normawaty (2016)
Light wavelengths and intensities affect the cortisol (stress hormone) levels in fish. Thus, this study aims to determine the optimum light wavelength and intensity to re-duce stress of juvenile sutchi catfish, Pangasianodon hypophthalmus. The sutchi cat-fish juveniles (35 days post hatching) were reared for 28 days (20 individuals/30 L) under five light wavelengths (white, blue, green, yellow, and red) with three light in-tensities (1.40 × 10-3, 1.40 × 10-2, and 1.40 × 100 μmoles/m²/s) in triplicates. The sutchi catfish juveniles were anesthetized at the end of rearing experiment. Cortisol hormones were extracted by homogenization and the cortisol levels of sutchi catfish juveniles were determined using ELISA kit. The results from the present study showed that light wavelengths had significant difference on the cortisol levels of sutchi catfish. Light wavelengths of green, yellow and red had significantly higher cortisol levels than light wavelengths of blue and white. For light intensities, sutchi catfish juveniles showed tendency for high cortisol level in 1.4 x 100 μmoles/m²/s compared to 1.4 x 10-2 μmoles/m²/s and 1.4 x 10-3 μmoles/m²/s. This result will be useful knowledge for rear-ing of sutchi catfish juveniles in hatchery thus improves their production rate.